S96. EXAMINING DIFFERENCES BETWEEN CURRENT CANNABIS CONSUMPTION AND COGNITIVE FUNCTIONING OF FIRST-EPISODE PSYCHOSIS PATIENTS: A RETROSPECTIVE STUDY - Pochiet, Gabrielle (Schizophr Bull, 2020)
BACKGROUND: Although growing research has observed a positive association between cannabis consumption and cognition in patients with first-episode psychosis (FEP), such better performance has not always been found across all cognitive domains. Furthermore, it remains unclear whether frequency of use is related to cognitive functioning in a dose-dependent manner. Understanding these associations may help to better manage cognitive impairments highly prevalent in FEP patients and inform prognosis. The aim of this study was to compare current cannabis use and cognitive functioning of FEP patients in a naturalistic setting. We hypothesized that FEP patients with current cannabis consumption (for the past 6 months or more) would present with higher cognitive performance scores compared to patients with no current consumption. METHODS: This cross-sectional, retrospective study included 192 current cannabis-using and 137 non-using patients at time of admission to a specialized early intervention clinic for FEP at the Douglas Mental Health University Institute in Montreal, Canada. Participants completed clinical and cognitive test batteries, including assessments of verbal memory, executive functioning, processing speed, working memory, attention, and visual memory. Cognitive domains were assessed using Weschler Memory Scale III and CogState Battery. Current cannabis consumption and frequency of use were assessed using the Chemical Use, Abuse, and Dependence Scale (CUAD). In addition to comparing status of cannabis consumption, four groups of FEP patients were analyzed according to frequency of use: 1) non-users (NU, n = 102), 2) light-users (LU, n = 21), 3) moderate-users (MU, n = 35), and heavy-users (HU, n = 64). Separate MANCOVA analyses were conducted to test the main effects of 1) current cannabis consumption (use vs non-use) and 2) frequency of cannabis use (none, light-use, moderate use, heavy use) on six cognitive domain performance scores. Age, sex, cigarette use, and cognitive battery type were entered as covariates, as they are known to influence neurocognitive scores. RESULTS: Between-group comparisons on demographic variables revealed statistically significant differences in age (with NU being older than LU) and cigarette use (with the HU having higher % of use). Contrary to our hypothesis, no significant differences were found between current users and non-users, even while controlling for potential confounds, F(6,143) =1.61, p=.149. When splitting the user group based on frequency of use, no significant differences were observed on cognitive performance, F(18,399.3) =.903, p=.575. DISCUSSION: Our findings reveal no significant differences between current cannabis consumption and cognitive functioning in a large representative sample of FEP patients at time of entry into a treatment clinic. This is consistent with previous studies that showed absence of differences in neurocognitive functioning between FEP cannabis users and non-users (e.g., Bugra et al., 2013). Other potential confounds such as the age of cannabis use onset, history of use and the different types of cannabis preparations may influence the present results and necessitate measurement in future investigations. The age differences observed may suggest that those who develop psychosis at a later age could be less predisposed to use cannabis. Alternatively, it is possible that light-use of cannabis somehow triggers the onset of psychosis, as is suggested by the literature that cannabis use is a component cause of developing psychosis.